Interpretación de datos gravimétricos del Bathurst Mining Camp - Sheephouse Brook Block, Canadá (2020)
The Bathurst Mining Camp (BMC) is one of the oldest mining districts in Canada when it comes to volcanogenic massive sulphide (VMS) deposits. This mining camp was the subject of the Target Geoscience Initiative Phase 3 (TGI3) project, in which the Geological Survey of Canada decided in 2006 to carry out a survey to acquire new gravimetric data in the BMC. The main objective of this study was to generate a gravimetric mesh that covers the entire mining field with an average spacing of 1 km, with the intention of improving the gravimetric knowledge that we had so far. All gravity data used in the current study were taken from the Geoscience Data Repository for geophysical data on the page of Natural Resources Canada (Canada - Geoscience Data, n.d.), these data are freely accessible to the public. The gravimetric data was treated assuming an average density of 2,77 cm3, due to the high presence of mafic igneous rocks causing a considerable increase in the average density of this area. In the Sheephouse Brook block four transects and a 3D model of these were made, using the GM-SYS Profile and 3D View tool respectively, from the Oasis Montaj - Geosoft. A 3D model combining the models obtained along the different transects helps the understanding of the different structures and formation that occur in the BMC, such as the synclines Nine Mile and Moose Lake, which in the area of study have the character of an open fold and a gentle one respectively. In addition, it is postulated the presence of a very dense unit which allows to create several of the models presented, which could have inclusions of some ultramafic dense rocks or the presence of a unit of basalts and mafic rocks.